Kinetika Adsorpsi Ion Cu²⁺ dengan Adsorben Silika Xerogel dari Abu Terbang - Mila Lusy Tri Nandi; Edi Nasra (Lembaga Yasin AlSys, 2025)
Contamination by heavy metal ions such as Cu²⁺ in water sources poses a serious environmental issue due to their toxic effects on living organisms. This study aims to evaluate the adsorption kinetics of Cu²⁺ ions using silica xerogel synthesized from fly ash. The synthesis was carried out via the sol-gel method, and material characterization was performed using X-Ray Fluorescence (XRF) to determine the silica content. The adsorption process was conducted in batch mode with contact time variations of 30, 60, 90, 120, 150, and 180 minutes. Analysis results showed that the fly ash contained 54.167% silica, and the optimal adsorption capacity was achieved at 150 minutes with a value of 44.982 mg/g. The adsorption kinetics were best described by the pseudo-second-order model, indicated by a coefficient of determination (R²) of 0.99947, suggesting that the adsorption process follows a chemisorption mechanism. These findings imply that silica xerogel derived from fly ash has significant potential as an effective adsorbent for environmental remediation of Cu²⁺ ion contamination.